Sexual dysfunction in irritable bowel syndrome - Sultana , Farhana; Algin, Sultana; Aftab, Hafeza (Bangladesh Journal of Medicine, 2024)
Background: Irritable bowel syndrome (IBS) is a common functional bowel disorder. The prevalence of IBS is more inwomen. It is often associated with extra-intestinal symptoms like psychosomatic symptoms and sexual dysfunction. This study investigated the frequency of extra intestinal manifestation especiallypsychosomatic symptoms and sexual dysfunction of irritable bowel syndrome in women. Methods: This is a descriptive crosssectional study was conducted in the Department of Gastroenterology , Dhaka Medical College Hospital from April 2022 to March, 2023. Patients were included following Rome IV criteria for IBS and face to face interviewed. Psychosomatic Symptoms Questionnaire (PSQ-39), the Arizona SexualExperience Scale were used for psychosomatic and sexual status respectively. Results: One hundred twenty patients participated, mean age was 36.43±9.91years, Majority (40% ) had higher secondary level education, predominant occupation was housewife (82.5%) , most of them (55%) living in urban area. Mean duration of illness was 4.28±2.217 years, diarrhea predominant IBS-D (53%) was most common.Among them 65% had psychosomatic symptoms, 56.7 % reported sexual symptoms. According to ASEX criteria no sex drive was found in 27.5%, weak sex drive in 24.2%, sexual arousal never occurred in 26.7%, difficult in sex 28.3%, no vaginal lubrication in 17.5%, difficult in orgasm 29.2%, orgasm never experienced in 26.7%, difficult to reach orgasm in 28.3%, satisfaction of orgasm was never in 30%, unsatisfying orgasm in 26.7% of them.About 75.3% population had perception that IBS as their cause of sexual dysfunction, 8.2% had incompetent male partner, 9.4% had their partner in abroad and 7.1% patients had familial disharmony, 14.2% had history of abstinent. Conclusion: In addition to bowel problems sexual dysfunction is common extra intestinal complaints in IBS patients. Requires special attention during management of IBS in women Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 168.